MEMBACA FOTO JENAZAH COVID-19 KARYA JOSHUA IRWANDI DENGAN PERSPEKTIF LITERASI VISUAL - Radityo Widiatmojo; Awan Setia Dharmawan (Institut Seni Indonesia Yogyakarta, 2021)
Reading Photograph of the Covid-19 Body by Joshua Irwandi using Visual Literacy. The photo of Joshua Irwandi's Covid-19 body went viral when influencer Anji posted Joshua's photo and gave negative comments. Various negative comments, interpretations and justifications from netizens actually represent challenges in the development of visual literacy in Indonesia, more specifically there is no literacy in terms of